The ruthless elimination of hurry - Comer, John Mark, 1980- (WaterBrook, 2019)
Outwardly, Comer appeared successful. But inwardly, things weren't pretty. The advice his mentor gave him wasn't what he expected: "Ruthlessly eliminate hurry from your life. Hurry is the great enemy of the spiritual life." But it was the answer Comer needed. Here he shows you how to stay emotionally healthy and spiritually alive, by discovering a slower, simpler way of life. -- adapted from Amazon.com info